Influence of ESG on Sustainability Reporting: Mediation Rule of Green Innovation and Investor Sentiment - Siregar, Inova Fitri; Ismail, Tubagus; Taqi, Muhammad; Soleha, Nurhayati (International Journal of Energy Economics and Policy, 2024)
This study aims to investigate if the quality of sustainability reporting is particularly influenced by a company’s commitment and approach to relevant environmental, social, and governmental (ESG) factors. Companies that seriously implement good sustainability reporting are likely to produce more detailed, relevant, and measurable ESG practices. The sample criteria were non-financial sector companies that had completed sustainability reports. This study collected 430 pieces of data from 215 companies. Data were collected from the 2021-2022 sustainability reports. The results show that ESG has a positive and significant effect on green innovation, investor sentiment, and sustainability reporting, and green innovation has a significant effect on sustainability reporting. However, investor sentiment does not significantly mediate the relationship between ESG and sustainability reporting. This study can help companies understand the factors that contribute to sustainability reporting. The limitation of this study is the development of theoretical models to anticipate the controversial debate behind the effect of ESG. Future research can combine and develop theoretical models on ESG and environmental uncertainty, which refers to the different, unpredictable, and constantly changing nature of the environment in which organizations operate. Environmental uncertainty can pose risks to organizations, including risks associated with supply chain disruptions and regulatory changes.